(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Supriyomo, Soviana S, Novianto D, Musyaffa MF, Tan S, Hadi UK. 2022. Morphological characteristic of malaria vector Anopheles aconitus (Family: Culicidae) revealed by advanced light and scanning electron microscope. Biodiversitas 23: 3546-3552. Anopheles aconitus (An. aconitus) is one of the primary vectors for malaria in several areas in Indonesia, especially in Java Island. Scanning electron microscope (SEM) is a powerful tool that can differentiate Anopheles spp. Morphology that is difficult to identify by using a light microscope only. The adult of An. aconitus used in this study have been reared in the laboratory. This research is conducted to better understand the Anopheles aconitus’ external morphology, such as the head, proboscis, wings, thorax and legs, using advanced light and SEM. Results from an advanced light microscope showed that An. aconitus has palpus with the same length as proboscis with one narrow basal end and two broad distal ends; meanwhile, the apical half of proboscis is pale. Anopheles aconitus has wings with four pale spots on the costa side. Legs are uniformly dark with only very narrow, rather faint pale bands at the joining of segments. Using SEM, we found several types of sensilla trichodea: short-sharp tipped, short-blunt tipped, and long-shaped tipped in antenna, apical proboscis, maxillary palps, abdomen, and legs. Antenna is also covered with microtrichia and sensilla. This research is important for basic necessity in fully understanding and determining of mosquito bionomic due to the development of effective and efficient mosquito vector control strategies.